Scientific And Educational Technologies In Human Capital Formation - Utiuzh, Irina; Spytsia, Natalia; Sinitsyna, Alla; Pavlenko, Natella (Տիգրան Մեծ)
The article deals with a constructive role of socio-humanitarian and philosophical knowledge in the system of natural science structures. It is proved that the relevance of socio-humanities and philosophy is a response to the challenges of the modern technology-based civilization, where exact and natural sciences call for the revival of a philosophic component in the education system and science. In the article, the main cause-and-effect relations that have resulted in modern societies in demand for revival of philosophic and socio-humanitarian knowledge in science and education are revealed. A new paradigm for the development of philosophic and socio-humanitarian knowledge is presented. The authors present the implementation results of new interdisciplinary dialogue in the system of socio- humanities and natural sciences within the Zaporizhzhia State Medical University (Ukraine), where the Department of Social Studies has adapted and implemented a number of projects in this area. One of which is the School for Young Lecturers – project in the framework of practice-oriented education. The article emphasizes that the return of social science to the higher education system and its role in science must be considered as a complex, multi-level process that should be studied and comprehended for its optimal implementation.
Keywords: Social philosophy